The artistic turn : a manifesto - Coessens, Kathleen; Crispin, Darla; Douglas, Anne, Dr. (Ghent, Belgium : Orpheus Instituut ; Leuven, Belgium : Distributed by Leuven University Press, 2009)
Despite innovative developments in research in-and-through the arts in the past decade, the emergent field of artistic research remains controversial, and is accepted with varying degrees of enthusiasm in academic institutions. It is our contention that the challenges and opportunities presented by this burgeoning discipline may be better understood by re-emphasising the centrality of the artist. Through a study of the interrelationship between artistic fields and theories of knowledge, and through some consciously metaphorical readings, we examine the contexts within which artistic research has developed.
Why art matters -- Artistic research and scientific method : two cultures? -- Deterritorializing the research space : the ways of knowing art -- The ship sailing out : practical navigation and the lure of "L'horizon chimérique" -- Doubts and vulnerability -- Why artistic research matters.
boek
Keywords: Musicology; Music -- Methodology; Musicians -- Research; Arts -- Research; Arts -- Methodology